2015
DOI: 10.1016/j.procir.2015.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-based Determination of Alternative CNC Machines for a Flexible Resource Allocation

Abstract: In case of an unplanned machine breakdown, alternative resources have to be found quickly to avoid delays in following process steps. In order to counter this, an automated determination of alternative CNC-machines and a reliable validation is proposed. First, a rough process description is extracted from the NC program. Second, a suitable machine is searched in an ontology based on the rough process description. The ontology contains a description of all needed properties of a machine and rules to derive the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies regarding the manufacturing ontology in relation to the PLM can be found in papers like [8][9][10][11][12], each aiming for a certain stage of the PLM like Design/Development, machine selection, assembly, etc.…”
Section: On the Concept Manufacturing Ontologymentioning
confidence: 99%
“…Studies regarding the manufacturing ontology in relation to the PLM can be found in papers like [8][9][10][11][12], each aiming for a certain stage of the PLM like Design/Development, machine selection, assembly, etc.…”
Section: On the Concept Manufacturing Ontologymentioning
confidence: 99%